The effects of metaphor awareness on L2 learners’ retention of English idiomatic phrases / Brandon Chai An Weng - Brandon Chai , An Weng (2019)
This study sought to examine the effects on idiom retention by raising the metaphor awareness of L2 learners of English. The results presented positive pedagogical implications for intentional (formal) vocabulary teaching. An explanatory sequential research design, with one experimental group and one control group was employed in this study, N = 42. A within-group analysis of the experimental method revealed that between the pre and delayed post-test levels (strict scoring), the experimental group’s participants’ retention of the taught idiomatic phrases had improved by 31%, although statistical significance was not achieved. A between-groups analysis comparing the experimental and conventional methods of teaching idioms showed that the overall differences between the two groups were not statistically significant as well, under both strict and lenient scoring schemes. However, qualitative analyses revealed mainly positive attitudes toward the experimental method, while mostly negative attitudes were attributed to the conventional “blind memorisation” method for learning idioms.